ROYAL THAI CONSULATE-GENERAL VISITS THAI ARTWORKS EXHIBITION AT MGTF - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
PENANG, 6 April 2017 The Royal Thai ConsulateGeneral in Penang, Her Excellency Ms. Ekajit Kraivichien visited the Muzium & Galeri Tuanku Fauziah (MGTF) at Universiti Sains Malaysia (USM) earlier today in conjunction with the Two Series of Artworks exhibition from Thailand.